ACADEMIC PUZZLE - THE RELATIONSHIP BETWEEN ORIGINALITY, PLAGIARISM AND SIMILARITY IN THE CONTENTS OF DOCTORAL THESES - Narcisa-Victoria DĂRĂBAN (Challenges of the Knowledge Society)
In a world where every individual strives to showcase his originality, peculiarities and traits that make him different from others through all possible means, whether we are talking about the style of clothing, the image on social media, hobbies, the language used, or the works read or created, this paper aims to discover how originality manifests in scientific works and what steps to follow in order to create the academic puzzle called a doctoral thesis, considering the pieces that don't seem to fit together, despite having multiple similar aspects: originality, plagiarism and similarity. These three concepts are of particular importance in the academic world, sparking intense discussions and within civil society in recent times, with profound implications for the integrity of research and the genuine understanding of individual academic contributions. In today’s information age, where access to resources and technologies is readily available to all, originality seems to constantly dilute, while the phenomenon of plagiarism is on the rise, becoming increasingly prominent and complex, diminishing trust in research studies and the work done. In the context in which doctoral theses should represent significant contributions to human knowledge, we aim that from this paper to clearly result the meaning and purpose of the three terms within the work intended to form the basis for awarding the doctoral title to its author .